Diagnosis of focal liver lesions with gadoxetic acid‐enhanced MRI: Is a shortened delay time possible by adding diffusion‐weighted imaging?. Issue 1 (24th September 2013) - Kim, Moon Young; Kim, Young Kon; Park, Hyun Jeong; Park, Min Jung; Lee, Won Jae; Choi, Dongil
<x xml:space="preserve">Abstract</x> Purpose To determine whether the diagnostic performance of combined gadoxetic acid‐enhanced dynamic phases and diffusion‐weighted imaging (DWI) is comparable to the standard protocol with hepatobiliary phase (HBP) and DWI for detection and characterization of focal liver lesions in chronic liver disease. Materials and Methods A total of 176 patients with 181 HCCs, 15 cholangiocarcinomas, and 32 benign lesions were included. Three combined gadoxetic acid‐enhanced and DWI sets (dynamic phases [arterial, portal, and 3‐min delay {3‐min set} and dynamic phases with 10‐min HBP [10‐min set] or 20‐min HBP [20‐min set]) were analyzed by two observers to determine the diagnostic accuracy and sensitivity in detection of malignancy, and ability for lesion characterization. Results There was a trend, although not statistically significant, toward highest diagnostic accuracy and sensitivity for detecting malignancies in the 20‐min set (mean, 0.945, 96.2), followed by the 10‐min set (0.937, 95.9), and the 3‐min set (0.923, 94.1) (P > 0.05). For lesion characterization, three image sets were equivalent (P > 0.05). Conclusion For lesion detection and characterization in chronic liver diseases, 3‐min set with DWI showed comparable efficacy to 10‐min or 20‐min set. However, the best diagnostic performance could be achieved by combination of all image sets. J. Magn. Reson. Imaging 2014;39:31–41. © 2013 Wiley Periodicals, Inc.